Fenomena Fenomena Alternatif Job Fresh Graduate Menjadi Ojek Online di Fakultas Sastra UM - Abidin, Zainal (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The presence of online motorbike taxis in our daily lives is a phenomenon that is commonplace in today's sophisticated era. Therefore, this research aims to find out the background of fresh graduates from the Faculty of Letters at the State University of Malang becoming online motorbike taxis and the challenges and opportunities they face when becoming online motorbike taxis. This research uses a qualitative method with a phenomenological approach and Coleman's rational choice theory, using 5 informants. Data collection techniques use interviews, observation and documentation. The research results show that the informant has reasons for becoming an online motorcycle taxi with a choice that is profit-oriented and wants to be productive after graduating from college.